Ethanol Modulates the Spontaneous Complex Spike Waveform of Cerebellar Purkinje Cells Recorded in vivo in Mice - Zhang, Guang-Jian; Wu, Mao-Cheng; Shi, Jin-Di; Xu, Yin-Hua; Chu, Chun-Ping; Cui, Song-Biao; Qiu, De-Lai (Frontiers in Cellular Neuroscience, 2017)
Cerebellar Purkinje cells (PCs) are sensitive to ethanol, but the effect of ethanol on spontaneous complex spike (CS) activity in these cells in vivo is currently unknown. Here, we investigated the effect of ethanol on spontaneous CS activity in PCs in urethane-anesthetized mice using in vivo patch-clamp recordings and pharmacological manipulation. Ethanol (300 mM) induced a decrease in the CS-evoked pause in simple spike (SS) firing and in the amplitude of the afterhyperpolarization (AHP) under current clamp conditions. Under voltage-clamp conditions, ethanol significantly decreased the area under the curve (AUC) and the number of CS spikelets, without changing the spontaneous frequency of the CSs or the instantaneous frequency of the CS spikelets. Ethanol-induced a decrease in the AUC of spontaneous CSs was concentration dependent. The EC50 of ethanol for decreasing the AUC of spontaneous CSs was 168.5 mM. Blocking N-methyl-D-aspartate receptors (NMDARs) failed to prevent the ethanol-induced decreases in the CS waveform parameters. However, blockade of cannabinoid receptor 1 (CB1) significantly suppressed the ethanol-induced effects on the CS-evoked pause in SS firing, amplitude of the AHP, spikelet number and the AUC of CSs. Moreover, a CB1 receptor agonist not only reduced the number of spikelets and the AUC of CSs, but also prevented the ethanol-induced inhibition of CS activity. Our results indicate that ethanol inhibits CS activity via activation of the CB1 receptor in vivo in mice, suggesting that excessive ethanol intake inhibits climbing fiber–PC synaptic transmission by modulating CB1 receptors in the cerebellar cortex.